High scavenger receptor class B type I expression is related to tumor aggressiveness and poor prognosis in lung adenocarcinoma: A STROBE compliant article. Issue 13 (March 2018) - Feng, Hong; Wang, Minghui; Wu, Changshun; Yu, Jinyu; Wang, Dan; Ma, Jian; Han, Junqing
Abstract : Abstract: Scavenger receptor class B type I (SR-B1) is highly expressed in a variety of cancers, including prostate, breast and ovarian. However, the relationship between SR-B1 and lung adenocarcinoma is unknown. We analyzed the expression of SR-B1 in a well-characterized lung adenocarcinoma tissue microarray by immunohistochemistry, in 90 cancerous and 90 adjacent normal lung tissues. Results showed that the positive expression rate of SR-B1 in cancer tissues (86/90, 96%) was significantly higher than that of adjacent tissues (50/90, 56%) ( P  < .001). And SR-B1 overexpression in lung adenocarcinoma tissue was significantly higher than that of adjacent normal tissue ( P <  .001), accounting for 67% of cases. This elevated SR-B1 expression was associated with AJCC stage ( P <  .001), T stage ( P =  .012), N stage ( P =  .002), and lymph node positivity ( P <  .001). The Kaplan–Meier survival analysis indicated that patients with high SR-B1 expression had a shorter overall survival ( P <  .001). On the multivariate analysis, SR-B1 was an independent prognostic factor for outcomes after adjustment for other prognostic factors ( P =  .038). In conclusion, high SR-B1 expression is associated with conventional pathologic parameters that represent tumor aggressiveness and may purport a poor clinical prognosis in lung adenocarcinoma.